WaterCopilot: a water management AI virtual assistant for the Limpopo River Basin Digital Twin - user guide V0 202410 - Vickneswaran, Keerththanan; Retief, H.; Padilha, R.; Dickens, Chris; Silva, Paulo; Ghosh, Surajit; Garcia Andarcia, Mariangel (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2024)
The Limpopo Digital Twin Water Management AI Virtual Assistant User Guide provides a practical guide for users to effectively navigate WaterCopilot, an AIpowered Copilot developed by the International Water Management Institute (IWMI) in collaboration with Microsoft Research. This guide offers clear instructions on using the Copilot to access crucial water-related data for the Limpopo River Basin, including rainfall insights, environmental flow alerts, and water availability.